2014
DOI: 10.21977/d910119060
|View full text |Cite
|
Sign up to set email alerts
|

“Unlocking My Creativity”: Teacher Learning in Arts Integration Professional Development

Abstract: This article examines the impact of two approaches to teacher professional development in arts integration-a summer institute model and a model combining the summer institute with instructional coaching. In an experimental design, the intervention trained third and fourth grade teachers to integrate visual arts and theater into reading curriculum. Findings suggest the coaching plus institute intervention had a greater impact on teacher confidence, use and frequency of arts integration than the institute-only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 15 publications
4
14
0
Order By: Relevance
“…In fact, all three, art learning, professional development, and academic outcomes, are inseparable when considering the impact of arts integration on an academic program (Scripp & Paradis, 2014). Professional development that is specific to arts integration can help to improve teachers' confidence, knowledge, knowledge and implementation in the classroom (Saraniero, Goldberg, & Hall, 2014). Teachers in Saraniero and colleagues' study (2014) who received professional development in arts integration reported they felt more creative and engaged in their teaching, were more focused in their lesson planning, and found that arts integration was an effective reading strategy.…”
Section: Professional Development In Arts Integrationmentioning
confidence: 99%
“…In fact, all three, art learning, professional development, and academic outcomes, are inseparable when considering the impact of arts integration on an academic program (Scripp & Paradis, 2014). Professional development that is specific to arts integration can help to improve teachers' confidence, knowledge, knowledge and implementation in the classroom (Saraniero, Goldberg, & Hall, 2014). Teachers in Saraniero and colleagues' study (2014) who received professional development in arts integration reported they felt more creative and engaged in their teaching, were more focused in their lesson planning, and found that arts integration was an effective reading strategy.…”
Section: Professional Development In Arts Integrationmentioning
confidence: 99%
“…The most cited challenge to classroom practitioner integration usage is time. This includes planning time, time to collaborate with arts specialists or other artistic teachers, and perceived time to execute arts integrated lessons and activities (LaJevic, 2013;Oreck, 2006;Saraniero, Goldberg, & Hall, 2014). Administrative support is also a contributing factor to integration frequency, as chronicled through different research designs (Bellisario and Donovan, 2012;Purnell, 2004;Van Eman et al, 2008).…”
Section: Review Of Related Literature On Arts Integrationmentioning
confidence: 99%
“…Practitioners describe a singular administrative focus on both high stakes tests (Bellisario & Donovan, 2012;Oreck, 2004;Oreck, 2006) and pre-scripted curriculum (Garvis & Pendergast, 2010;LaJevic, 2013;Saraniero et al, 2014;Van Eman et al, 2008) as deterrents to using an integrated approach. Finally, literature indicates that preservice and professional development training in arts integrated practices improves teacher comfort and self-efficacy with varied art forms (Oreck, 2004).…”
Section: Review Of Related Literature On Arts Integrationmentioning
confidence: 99%
“…Sustained in-depth collaborations help support implementation (Simpson, Herring, & Kelin, 2002). Furthermore, these types of coaching practices have been found to increase teacher confidence and implementing art practices in the classroom (Saraniero & Goldberg, 2014).…”
Section: Perspectives or Theoretical Frameworkmentioning
confidence: 99%